Resonance Raman spectroscopy as an in situ probe for monitoring catalytic events in a Ru–porphyrin mediated amination reaction. Issue 10 (12th April 2016) - Zardi, Paolo; Gallo, Emma; Solan, Gregory A.; Hudson, Andrew J.
Abstract : A method to monitor the mechanisms of homogeneously-catalysed reactions under conditions of refluxing solvents using resonance Raman spectroscopy. Abstract : Resonance Raman microspectroscopy has been widely used to study the structure and dynamics of porphyrins and metal complexes containing the porphyrin ligand. Here, we have demonstrated that the same technique can be adapted to examine the mechanism of a homogeneously-catalysed reaction mediated by a transition–metal–porphyrin complex. Previously it has been challenging to study this type of reaction using in situ spectroscopic monitoring due to the low stability of the reaction intermediates and elevated-temperature conditions. We have made a straightforward modification to the sample stage on a microscope for time-lapsed Raman microspectroscopy from reaction mixtures in these media. The allylic amination of unsaturated hydrocarbons by aryl azides, which can be catalysed by a ruthenium–porphyrin complex, has been used as an illustrative example of the methodology. The mechanism of this particular reaction has been studied previously using density-functional theory and kinetic approaches. The Raman measurements support the mechanism proposed in the earlier publications by providing the first experimental verification of a precursor reaction complex between the aryl azide and the ruthenium metal ion, and evidence for the formation of a mono -imido intermediate complex under conditions of high concentration of the reactant olefin.